The Role of Creative Publicity in Different Periods of the COVID-19 Outbreak in China: Taking the Creative Publicity of Chinese Poetry as an Example - Jia, Dandan; Sun, Cuicui; Zhou, Zhijin; Zhao, Qingbai; Yu, Quanlei; Liu, Guanxiong; Wang, Yi (Frontiers in Psychology, 2021)
When humans are confronted with an epidemic situation or a continuous natural disaster, success depends largely on how critical information is conveyed to as many people as possible, how individuals’ emotional experiences of the crisis are elicited, and how their behaviors are directed going forward. Efficient publicity is key to successful epidemic prevention and control. This study explores the role of creative publicity by comparing the influence of creative publicity and general publicity in different periods of the COVID-19 outbreak in China. The effects of creative and general publicity differed across varying periods of the COVID-19 outbreak. Specifically, compared to general publicity, creative publicity had a significant impact on individuals’ emotional arousal in the early period of the COVID-19 outbreak while it significantly promoted individuals’ emotional arousal, behavioral regulation, and willingness to actively disseminate information in the middle period. In the stable period of the COVID-19 outbreak, creative publicity performed better than general publicity in regulating individuals’ behavior. On the other hand, general publicity was more effective than creative publicity in regulating individuals’ behavior and actively disseminating information about the epidemic in the early period of the COVID-19 outbreak. In conclusion, creative and general publicity had differing effects in different periods of the COVID-19 outbreak, which may relate to the characteristics of the publicity format and people’s psychological conditions in different periods of the COVID-19 outbreak.